Optimum inter-release time analysis for non-preemptive periodic task set. (3rd April 2017) - Pon Pushpa, S. Ewins; Manamalli, D.
Abstract: Tasks in a real-time system must be executed within its deadline to produce functionally correct results in a timely manner. Therefore, the behavior is strongly dependent upon the inter-release time of the task comprising the task set. This paper proposes system design methodology to achieve optimum schedulability for a non-preemptive periodic task set, deriving inter-release time from schedulability conditions. First, the methodology is applied to uniprocessor architecture and later generalized for multiprocessor environment. As a technical contribution, success ratio and effective processor utilization are analyzed for a uniprocessor and multiprocessor architecture modeled using Unified Modeling Language-Real Time.